2015
DOI: 10.1007/s00256-015-2267-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeted computerised tomography scanning of the ankle syndesmosis with low dose radiation exposure

Abstract: Our study describes a reliable new CT scanning technique for the distal tibiofibular syndesmosis using only five cuts and a low-radiation-dose protocol. Clinical correlation of the findings on the scan with functional outcomes suggests that routine post-operative CT of the syndesmosis is probably not justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…Traditionally, nonweightbearing 2D CT evaluation of the tibiofibular joint space has relied on drawing 3 lines from the anterior, middle, and posterior borders of the fibula to the incisura in the axial plane, but such approaches have demonstrated a wide range of normal values. 3,7,9,10,13,15-17 Furthermore, only one such study by Lepojärvi et al 13 explored bilateral values, finding no difference based on laterality. The alternative measurement techniques we incorporated in this study were adopted from reports that investigated syndesmosis malreduction, and were explicitly chosen because of their high interrater reliability scores.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, nonweightbearing 2D CT evaluation of the tibiofibular joint space has relied on drawing 3 lines from the anterior, middle, and posterior borders of the fibula to the incisura in the axial plane, but such approaches have demonstrated a wide range of normal values. 3,7,9,10,13,15-17 Furthermore, only one such study by Lepojärvi et al 13 explored bilateral values, finding no difference based on laterality. The alternative measurement techniques we incorporated in this study were adopted from reports that investigated syndesmosis malreduction, and were explicitly chosen because of their high interrater reliability scores.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers found that CT scans hold the advantage over radiographs for the diagnosis of lesions in the DTS [ 13 , 19 ] (Fig. 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TFCS was measured in the resulting axial image (Fig. 3C) using the same method that was previously reported for CT [10,14,17]. The first reference point was chosen on the lateral prominence of the anterior tibial tubercle.…”
Section: Methodsmentioning
confidence: 99%